(The Influence of Extraction Temperature Treatment on Cocoa Butter Quality Characteristics) - Lukman Junaidi; Agus Sudibyo; Tiurlan F.Hutajulu; Dede Abdurahman (Balai Besar Industri Agro, 2008)
Research on the influence of Extraction Temperature Treatment on Cocoa Butter Quality Characteristics gas been conducted. The study was focused on the effect of treatment of the extraction temperature range when conducted hydraulic pressing on cocoa nibs. The variation of temperature range was chosen at: 40'-50'C: 50'-60'C: 60'-70'C: 70'-80'C: 80'-90'C. The research showed that treatment of extraction temperature level give an influence on the cocoa butter quality characteristics e.g: moisture content, FFA, sapnification value, iodine number and refrective index. The results showed that moisture content of cocoa butter extracted decrease with increasing of ectraction temperature, while FFA, saponification value, iodine number and refractive index increase with increasing of extraction temperature.The treatment of extraction temperature level also give influence on the proportion of fatty acid type (saturated fatty acid and unsaturated fatty acid) on coca butter. The proportion of total unsaturated fatty acids tend to decrease with increasing of extraction temperature. On the other hand the proportion of total saturated fatty acids and yield of extraction tend to increase with increasing of eextraction temperature.